Tingkat Pengetahuan Ibu Hamil tentang HIV/AIDS dengan Perilaku Pemeriksaan Test PITC (Provider Initiated Test and Counselling) di Puskesmas Sleman Yogyakarta - Annisaa’ Nurmasari; Fatimah Fatimah; Febrina Suci Hati (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2015)
HIV infection in pregnant women can threaten the life of the mother and the mother can transmit the virus to their babies. Sleman PHC registered 2 people including one pregnant woman and one women of childbearing age in the year of 2014. Incidence of pregnant women suffering from HIV-AIDS in 2014 is 1 patients and detected from PITC test results for 7 weeks in a row is 1 patient. And in January year of 2015 found 1 patient with 3 times test and the results was positive. The purpose of this study was to determine relationship between Knowledge Level of Pregnant women about HIV/AIDS and Behaviour of PITC (Provider Initiated Test and Counselling) test. This study was a quantitative analysis of correlation with cross-sectional design. The population of this study were all pregnant women checkups at the health center in Yogyakarta Sleman. The sampling technique was used accidental sampling study which consisted of 72 respondents. The analysis used univariate and bivariate. The results showed that most respondents aged 20-35 (72.2%), senior high school education (47.2%) and work as a housewife (IRT) (38.9%). Most respondents have good knowledge about HIV/AIDS were 50 respondents (69.4%). Most respondents perform checks PITC were 71 respondents (98.6%). There was no relationship between knowledge level of pregnant women about HIV/AIDS and Behaviour of PITC (p-value=0.243>0.005). In Conclusion, There was no relationship between knowledge level of pregnant women about HIV/AIDS and Behaviour of PITC in Sleman, Yogyakarta.